2020
DOI: 10.1177/1078155220924084
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of COVID-19 infection in elderly patient with melanoma on nivolumab

Abstract: Outbreak of the new type coronavirus infection, known as coronavirus infection 2019 (COVID-19), has begun in December 2019, in Wuhan, China. As of today, 3 April 2020, 972,640 people affected and 50,325 people died from Severe Acute Respiratory Syndrome-Coronavirus 2. There is not any standard treatment for coronavirus infection 2019; however, there are promising data for hydroxychloroquine and some anti-retroviral drugs. Programmed death-1 (PD-1)/programmed death ligand-1 (PDL-1) pathway is an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
(16 reference statements)
0
21
0
5
Order By: Relevance
“…21 Yekedüz et al reported a 75-year-old female metastatic melanoma (BRAF wild-type) patient with multiple comorbidities, contracting SARS-CoV-2 infection. 22 The patient developed severe respiratory symptoms related to COVID-19 while she was on nivolumab. She was discharged with a good clinical condition on the fifth day of the favipiravir and hydroxychloroquine treatment.…”
Section: Melanoma Screening In the Era Of Covid-19mentioning
confidence: 99%
“…21 Yekedüz et al reported a 75-year-old female metastatic melanoma (BRAF wild-type) patient with multiple comorbidities, contracting SARS-CoV-2 infection. 22 The patient developed severe respiratory symptoms related to COVID-19 while she was on nivolumab. She was discharged with a good clinical condition on the fifth day of the favipiravir and hydroxychloroquine treatment.…”
Section: Melanoma Screening In the Era Of Covid-19mentioning
confidence: 99%
“…After screening the title and abstract, 1556 were excluded, and the full text of the remaining 63 articles was reviewed. Among these, 18 studies reported ICI use in cancer patients and prognosis of COVID-19 infection (5,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The 18 articles consisted of 9 cohort studies, 5 case series and 4 case reports.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, there has been a recently reported case of a patient taking nivolumab who was infected by coronavirus infection 2019 [ 80 ]. Despite old age and several comorbidities, she had a good clinical course without pneumonia.…”
Section: Discussionmentioning
confidence: 99%